Common Turkic Vocabulary of the Yakut Language: Words Denoting Animal Body Parts (Comparative Historical Analysis) - N. V. Malysheva; I. A. Danilov (Вестник Кемеровского государственного университета, 2019)
The article discusses linguistic contacts of the Turkic languages. The research was based on the common Turkic vocabulary of the Yakut language, namely words denoting animal body parts. The paper focuses on the comparative-historical aspect of the ancient Turkic and modern Turkic languages. The authors described the lexical-semantic and phonostructural features of Yakut words denoting animal body parts that have a common Turkic origin. The methods included continuous sampling method from lexicographic sources, as well as descriptive and comparative methods. The semantic transitions of Turkic lexical reflexes from the Praturk system to the modern form revealed that words denoting animal body parts represent the most ancient layer of the Yakut vocabulary. It consists of vocabulary common for most Turkic languages and belongs to stable categories. As part of the phonological analysis, the authors determined phonostructural types and characteristics of the phonological system of lexical reflexes, the nature of the stability and variability of lexemes, and the main causes of the instability of the phonostructures of the word stems of other Turkic languages in the Yakut language. An analysis of the lexical-semantic features of the Yakut words for animal body parts in comparison with their lexical parallels in other Turkic languages revealed the nature of stability and variability of the lexical meanings of the stems for specific Turkic language.